ECONOMICAL POTATO PRODUCTION ACCORDING TO THE ARIMA MODELING APPROACH FOR CLIMATE ADAPTATION - Simić, Divna; Janković, Snežana; Popović, Dragana B.; Cvijanović, Vojin; Tolimir, Nataša (Economics of Agriculture, 2025)
In is evident that global climate change, marked by decreased rainfall and higher temperatures affecting potato economical production, therefore they are yield projections are a crucial element in agricultural planning. Climate change, especially drought, poses significant challenges, necessitating adaptive strategies to mitigate adverse impacts. Potatoes, as a vital food crop, hold exceptional nutritional, biological, agronomic, and economic importance. This study aims to project potato production, average yields, and cultivated areas in Serbia over the next three years using ARIMA models based on 19 years of time-series data. The model’s focus on short-term projections (2024–2026) aligns with Serbia’s need for immediate climate adaptation strategies. Model performance was validated using RMSE and AIC/ BIC metrics, with comparative analysis against ETS benchmarks. The results inform strategic responses to climate risks, provide a valuable approach to yield projection, advancing sustainable agriculture, food security, and facilitating complex production planning.